Bi-level optimal scheduling of virtual energy station based on equal exergy replacement mechanism. (1st December 2022) - Ding, Jianyong; Gao, Ciwei; Song, Meng; Yan, Xingyu; Chen, Tao
Highlights: EQC is used to unify the heterogeneous energy in the form of exergy. Equal exergy replacement mechanism for unification of heterogeneous energy in value. Exchange any form of energy anytime for customers to reduce the energy cost. Uncertainty of price quantified by IGDT to reduce the risk of VES. Abstract: Integrated Demand Response (IDR) is an effective way to make full use of the resources of the integrated energy system (IES) to achieve a positive interaction between supply and demand. Energy cascade utilization is one of the important technical principles of the IES to improve energy utilization efficiency and realize comprehensive benefit optimization. The design of an incentive mechanism is an important prerequisite for realizing IDR. When formulating the incentive mechanism, the coupling between the conversion efficiency of multiple energy sources and the depreciation of energy quality in the process of energy cascade utilization should be comprehensively considered. The exergy is the index that can evaluate the engineering value of any form of energy. Therefore, this paper unifies the multiple heterogeneous energy sources in the IES in the form of exergy through the energy quality coefficient. To more accurately reflect the difference in energy value of multiple heterogeneous energy sources during the time of invocation, an equal exergy replacement mechanism is designed according to the principle of high energy quality and high price. The regulated energy of the customer participating in the IDR is stored in the form of exergy, and the customer can exchange any form of energy at any time under the same exergy. On this basis, a bi-level optimal scheduling model for virtual energy station (VES) to participate in the day-ahead market is established, which realizes the improvement of multi-subject interests. And use Information Gap Decision Theory (IGDT) to deal with the risks posed by uncertainty in day-ahead market prices. Finally, the case study shows that the designed incentive mechanism can further reduce the energy purchase cost of customers, and VES can obtain higher benefits than only providing internal energy sales services. The IGDT method can reduce operational risk, which verifies the feasibility of the method.